The Catalytic Characterization of Rare Earth Complexes Involving Silylene-Bridged Fluorenyl - MEI, LUO; HUAI-ZHU, MA; QING-DE, SU (Asian Journal of Chemistry, 2010)
A group of rare earth complexes involving silylene-bridged fluorenyl have been synthesized; they can catalyze a series of methacrylate polymerization. From the results we can conclude that these kinds of complexes are highly active catalysts.